Case Report: “Primary Immunodeficiency”—Severe Autoimmune Enteropathy in a Pediatric Heart Transplant Recipient Treated With Abatacept and Alemtuzumab - Kalaidina, Elizaveta; Utterson, Elizabeth C.; Mokshagundam, Deepa; He, Mai; Shenoy, Shalini; Cooper, Megan A. (Frontiers in Immunology, 2022)
Disorders of immune dysregulation following heart transplantation in children have been reported; however, the management of such disorders remains uncertain and challenging. In this case report, we describe a clinical course of a child with severe autoimmune enteropathy after a heart transplant in infancy and detail a treatment approach with abatacept and alemtuzumab. A 21-month-old girl with a medical history of congenital dilated cardiomyopathy and heart transplantation at 2 months was evaluated for chronic hematochezia. The patient underwent an extensive workup, including endoscopic biopsy which showed crypt apoptosis, similar to that seen with graft-versus-host disease (GVHD). Results of her immune workup were consistent with status post-thymectomy but also demonstrated evidence of immune dysregulation. Specifically, her immune phenotype at diagnosis demonstrated T-cell lymphopenia, restricted TCR repertoire and skewing of T-cell compartment toward memory phenotype, increase in serum soluble ILR2a, and hypergammaglobulinemia. In the absence of response to more standard immune modulation, the patient was treated with CTLA4-Ig (abatacept), followed by a combination of abatacept and a JAK inhibitor and, finally, a combination of abatacept and alemtuzumab. Following therapy with alemtuzumab, the patient achieved remission for the first time in her life. Her clinical course was complicated by a relapse after 6 months which again readily responded to alemtuzumab. Ultimately, despite these remissions, the patient suffered an additional relapse. This case highlights the challenges of neonatal thymectomy and adds new insights into the pathogenesis, diagnosis, and management of severe autoimmune enteropathy in pediatric heart transplant recipients.